Managing sport organizations : responsibility for performance - Covell, Daniel, 1963-; Walker, Sharianne; Hamakawa, Curt (New York : Routledge, 2019)
Now in a fully revised and updated fourth edition, Managing Sport Organizations introduces the fundamentals of sport management across every industry sector, from youth and intercollegiate sport to professional leagues. Bridging the gap between theory and practice, it covers every key topic, issue and concept in contemporary sport management, including understanding management and its relationship to sport strategy decision making organizational design leadership human resource management managing change facility management sport media and new technologies This new edition contains expanded coverage of current topics such as international sport, ethics, new technologies and career pathways in sport management. Each chapter includes a full range of useful features, such as case studies, career insights, management exercises, study questions and definitions of key terms and concepts. No other textbook combines the rigor of the business school with the creativity and dynamism of modern sport business. Accompanied by additional online resources, this is the perfect foundation for any course in sport management, sport administration or sport business.
'Third edition published by Routledge 2013'--T.p. verso.
Includes webography.
OCLC-licensed vendor bibliographic record.
Keywords: Sports administration; Sports administration -- United States